2018
DOI: 10.3389/fendo.2018.00223
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Features of Papillary Thyroid Carcinomas According to Their Subtypes

Abstract: BackgroundThe ultrasonographic characteristics and difference for various subtypes of papillary thyroid carcinoma (PTC) are still unclear. The aim of this study was to compare the ultrasonographic features of PTC according to its subtype in patients undergoing thyroid surgery.MethodsIn total, 140 patients who underwent preoperative thyroid ultrasonography (US) and thyroid surgery between January 2016 and December 2016 were included. The ultrasonographic features and the Korean Thyroid Imaging Reporting and Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Several studies reported that, prognosis of patients with PTCs may be associated with both clinical features and pathological variants [13][14][15]. However, US characters of various PTC subgroups are still insufficient [15,16], even though the method was widely used as the primary method in evaluating thyroid lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that, prognosis of patients with PTCs may be associated with both clinical features and pathological variants [13][14][15]. However, US characters of various PTC subgroups are still insufficient [15,16], even though the method was widely used as the primary method in evaluating thyroid lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why the follicular variant of PTC (FVPTC) has a very low frequency of microcalcifications (PBs) [ 69 ]. When FVPTC is infiltrative, the frequency of calcification can be higher but is rare in the encapsulated FVPTC [ 56 , 57 ]. Diffuse sclerosing variant of papillary thyroid carcinoma (DSVPTC) is an uncommon variant of PTC, characterized by diffuse involvement of one or both lobes of the thyroid gland [ 70 ].…”
Section: Calcification In Different Types Of Thyroid Cancermentioning
confidence: 99%
“…The classic variant is the most common PTC variant (32–49%), and the BRAF V600E mutation is the most frequent (90%) genetic driver of this variant [28,29,30]. A typical US pattern for this PTC subtype includes hypoechogenicity, spiculated/microlobulated margins, microcalcifications, non-parallel orientation, and mixed-type non-increased vascularity [31].…”
Section: Genetic Drivers and Sonographic Pattern Of Different Varimentioning
confidence: 99%
“…Microcalcifications are often absent, but macrocalcifications are found in 20% of tumors. A non-parallel orientation is very characteristic, and vascularity is mixed in most patients and increased in half of the cases [31].…”
Section: Genetic Drivers and Sonographic Pattern Of Different Varimentioning
confidence: 99%